2009
DOI: 10.1590/s1415-47572009005000089
|View full text |Cite
|
Sign up to set email alerts
|

Chromosome studies in Orchidaceae from Argentina

Abstract: The center of diversity of Argentinean orchids is in the northeast region of the country. Chromosome numbers and karyotype features of 43 species belonging to 28 genera are presented here.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
17
0
2

Year Published

2011
2011
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 17 publications
4
17
0
2
Order By: Relevance
“…It is a diploid taxon with 2n = 28 chromosomes. In agreement, Daviña et al (2009) reported the same number and Grabiele et al (2011a) found a regular meiotic behavior and n = 14 bivalents for these Argentinian accessions of C. calophyllus. The karyotype, composed by 18m + 10sm chromosomes, is unimodal (A 2 = 0.20; R = 1.92) and symmetrical (A 1 = 0.32; r>2 = 0.29; i = 40.01) and belongs to Stebbins' category 2A; the pair no.…”
Section: Resultssupporting
confidence: 79%
See 4 more Smart Citations
“…It is a diploid taxon with 2n = 28 chromosomes. In agreement, Daviña et al (2009) reported the same number and Grabiele et al (2011a) found a regular meiotic behavior and n = 14 bivalents for these Argentinian accessions of C. calophyllus. The karyotype, composed by 18m + 10sm chromosomes, is unimodal (A 2 = 0.20; R = 1.92) and symmetrical (A 1 = 0.32; r>2 = 0.29; i = 40.01) and belongs to Stebbins' category 2A; the pair no.…”
Section: Resultssupporting
confidence: 79%
“…It is a diploid species displaying 2n = 28 chromosomes. In agreement, Daviña et al (2009) reported the same number and Cerutti et al (2004) found a regular meiotic behavior and n = 14 bivalents for these Argentinian accessions of C. elatus. Other counts in this taxon found n = 14 bivalents and 2n = 28 for NE Argentina plants, in addition to 2n = 30 and 2n = 45 (45?, see below) for Brazilian and Misiones materials, respectively (Martinez 1981) added to 2n = 28 from NE Brazil populations (Felix & Guerra 2005).…”
Section: Resultssupporting
confidence: 77%
See 3 more Smart Citations